Pyrene based conjugated materials: synthesis, characterization and electroluminescent properties - Salunke, Jagadish K.; Sonar, Prashant; Wong, F. L.; Roy, V. A. L.; Lee, C. S.; Wadgaonkar, Prakash P. (Physical Chemistry Chemical Physics, 2014)
In this work, three novel pyrene cored small conjugated molecules, namely 1,3,6,8-tetrakis(6-(octyloxy)naphthalene-2-yl) pyrene (PY-1), 1,3,6,8-tetrakis((E)-2-(6-(n-octyloxy) naphthalene-2-yl) vinyl) pyrene (PY-2) and 1,3,6,8-tetrakis((6-(n-octyloxy) naphthalene-2-yl) ethynyl) pyrene (PY-3) have been synthesized by Suzuki, heck and Sonogashira organometallic coupling reactions, respectively. The effects of single, double and triple bonds on their optical, electrochemical, and thermal properties are studied in detail. These all materials are fluorescent and they have been used in organic light-emitting diodes (OLEDs) and their electroluminescent properties have been studied.

Phenothiazine and carbazole substituted pyrene based electroluminescent organic semiconductors for OLED devices - Salunke, Jagadish K.; Wong, F. L.; Feron, Krishna; Manzhos, Sergei; Lo, Ming Fai; Shinde, Durgaprasad; Patil, Abhijeet; Lee, C. S.; Roy, V. A. L.; Sonar, Prashant; Wadgaonkar, Prakash P. (Journal of Materials Chemistry C, 2016)
Due to their easy availability, low cost and opportunities for exploiting reactions of bromo substituents, 1,3,6,8-tetrabromopyrene has attracted major attention in the organic electronics community for designing and constructing novel classes of pyrene based organic semiconducting functional materials. In the present work, 1,3,6,8-tetrabromo pyrene was transformed into the corresponding tetrasubstituted carbazole and phenothiazine derivatives using the classical Suzuki coupling reaction. These newly synthesized materials with a carbazole substituent (PY-CA) and a phenothiazine substituent (PY-PH) were characterised thoroughly and were successfully used as an active light-emitting layer in organic light emitting diodes which resulted in blue and green emission with promising device performance. PY-CA exhibited the maximum brightness at around 2500 cd m(-2) and the power efficiency of 1.5 lm W-1 while that of PY-PH exhibited 2116 cd m(-2) and 0.45 lm W-1 respectively.

New pyrene cored small organic molecule with a flexible alkyl spacer: a potential solution processable blue emitter with bright photoluminescence - Valsange, Nitin G.; Wong, F. L.; Shinde, Durgaprasad; Lee, C. S.; Roy, V. A. L.; Manzhos, Sergei; Feron, K.; Chang, Samuel; Katoh, Ryuzi; Sonar, Prashant; Wadgaonkar, Prakash P. (New Journal of Chemistry, 2017)
A new pyrene cored small organic molecule viz. 1,3,6,8-tetrakis(4-((5-(9H-carbazol-9-yl) pentyl)oxy) phenyl)pyrene (PY-II) was designed and synthesized. The carbazole moiety with an alkyl spacer was introduced at 1, 3, 6 and 8 positions of the pyrene core to improve the charge transport properties and solution processability. PY-II exhibited excellent solubility in common organic solvents and high thermal stability up to 345 degrees C. The photoluminescence quantum yield (PLQY) of PY-II in solution was found to be 0.9 with bright blue emission near 450 nm which is just appropriate for the human eye. The solution processed non-doped OLED device fabricated using PY-II as an emissive layer afforded a pure blue emission with CIE coordinates of 0.16 and 0.16, a power efficiency of 0.17 lm W-1, a maximum current efficiency of 0.41 cd A(-1) and a maximum brightness of 202 cd m(-2).